Generation of α-Particle Beams With a Multi-kJ, Peta-Watt Class Laser System - Margarone, Daniele; Morace, Alessio; Bonvalet, Julien; Abe, Yuki; Kantarelou, Vasiliki; Raffestin, Didier; Giuffrida, Lorenzo; Nicolai, Philippe; Tosca, Marco; Picciotto, Antonino; Petringa, Giada; Cirrone, Giuseppe A. P.; et al. (Frontiers in Physics, 2020)
We present preliminary results on generation of energetic -particles driven by lasers. The experiment was performed at the Institute of Laser Engineering in Osaka using the short-pulse, high-intensity, high-energy, PW-class laser. The laser pulse was focused onto a thin plastic foil (pitcher) to generate a proton beam by the well-known TNSA mechanism which, in turn, was impinging onto a boron-nitride (BN) target (catcher) to generated alpha-particles as a result of proton-boron nuclear fusion events. Our results demonstrate generation of -particles with energies in the range 8-10 MeV and with a flux around 5 e9 sr-1.